2014
DOI: 10.1016/j.matbio.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy stimulates syndecan-1 shedding: A potentially negative effect of treatment that may promote tumor relapse

Abstract: In patients with multiple myeloma, the heparan sulfate proteoglycan syndecan-1 (CD138) is shed from the surface of tumor cells and accumulates in the serum and within the extracellular matrix of the bone marrow where it promotes tumor growth and metastasis. In the present study we discovered that commonly used anti-myeloma drugs stimulate syndecan-1 shedding both in vitro and in animals bearing myeloma tumors. Enhanced shedding is accompanied by increased syndecan-1 synthesis prior to drug induced tumor cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 43 publications
0
55
0
1
Order By: Relevance
“…We recently demonstrated that chemotherapy elevates shedding of syndecan-1 in myeloma [16]. Because heparanase (HPSE) is known to enhance syndecan-1 shedding, we investigated whether chemotherapy was inducing heparanase expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that chemotherapy elevates shedding of syndecan-1 in myeloma [16]. Because heparanase (HPSE) is known to enhance syndecan-1 shedding, we investigated whether chemotherapy was inducing heparanase expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chemotherapy often has undesirable side effects and in some cases chemotherapy has been shown to actually lead to enhanced tumor growth and resistance [14, 15]. We recently demonstrated that chemotherapy induces syndecan-1 shedding from tumor cells [16]. We also recently demonstrated that in myeloma patients, tumor cells that survive past chemotherapy had dramatically elevated levels of heparanase expression compared to cells harvested prior to therapy [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of ADAM10 and ADAM17 inhibitors was shown to ameliorate the response to chemotherapy treatments in different in vivo models of cancer (57,58), and ADAM inhibitors were used in clinical trials in breast cancer patients (59). Of interest, combined treatment using chemotherapy and metalloproteinase inhibitors recently was proposed as a therapeutic regimen in MM, because drug-induced ADAM-mediated CD138 release was shown to promote tumor growth (60). Overall, our findings suggest that targeting of metalloproteinases in conjunction with chemotherapy could be exploited for NK cell-based immunotherapeutic approaches, thus contributing to avoid the escape of malignant cells from stress-elicited immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD163 is, at least in part, generated as a result of cleavage by the enzyme a disintegrin and metalloproteinase 17 (ADAM17) [26], which may also be involved in shedding of CD138/syndecan-1 from MM plasma cells [27]. The mechanism for generation of sMR in humans is not known.…”
Section: Discussionmentioning
confidence: 99%